2021
DOI: 10.46309/biodicon.2021.991685
|View full text |Cite
|
Sign up to set email alerts
|

Body size and age structure of Lacerta agilis LINNAEUS, 1758 (Reptilia: Lacertidae) from two different populations in Turkey

Abstract: Age structure and longevity in 47 museum specimens (31 females and 16 males) of Lacerta agilis from two different populations in Turkey were skeletochronologically studied. The mean SVL of males was not significantly different from those of females, although intersexual differences in body size are female-biased. The age structure ranged from 3 to 6 years in male individuals, and 3 to 8 years in females. Age at sexual maturity was 2 years for males, while females reached sexual maturity after the third year of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…On the other hand, female specimens of L. media have higher mean age compared with those male specimens. Findings of L. viridis show similarity to the L. agilis that reached maturity at 2 years, while females attained at the third year of their lifetime (Candan, 2021; Guarino et al, 2010), like in Daghestan specimens of same species (Roitberg & Smirina, 2006a). Similarly, Schreiber's green lizards have been reported to reach maturity at the age of 3 years (Luís et al, 2004).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…On the other hand, female specimens of L. media have higher mean age compared with those male specimens. Findings of L. viridis show similarity to the L. agilis that reached maturity at 2 years, while females attained at the third year of their lifetime (Candan, 2021; Guarino et al, 2010), like in Daghestan specimens of same species (Roitberg & Smirina, 2006a). Similarly, Schreiber's green lizards have been reported to reach maturity at the age of 3 years (Luís et al, 2004).…”
Section: Discussionmentioning
confidence: 78%
“…It was estimated that individuals of the L. media live up to 10 years, whereas both sexes of L. viridis live for 8 years. Contrarily, males and females of the congener Lacerta agilis have lifespan of 7 and 8 years, respectively (Candan, 2021; Guarino et al, 2010; Roitberg & Smirina, 2006b). Similarly, the minimum longevity for Iberian Emerald Lizard, Lacerta schreiberi has been reported to be 7 and 8 years by Luís et al (2004) for males and females, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). In reptiles, body length correlates to age due to an undetermined growth throughout their life (Candan 2021). Indeed, assuming 325 mm as SVL at sexual maturation (Lucchini et al 2020;Espasandín et al 2022) we indicate that helminths were mostly found in adults of V. seoanei.…”
Section: Biological and Eco-geographic Factors Related To Helminth Oc...mentioning
confidence: 99%